Intrarenal Renin–Angiotensin System Involvement in the Pathogenesis of Chronic Progressive Nephropathy—Bridging the Informational Gap Between Disciplines. (October 2019) - Obert, Leslie A.; Frazier, Kendall S.
Chronic progressive nephropathy (CPN) is the most commonly encountered spontaneous background finding in laboratory rodents. Various theories on its pathogenesis have been proposed, but there is a paucity of data regarding specific mechanisms or physiologic pathways involved in early CPN development. The current CPN mechanism of action for tumorigenesis is largely based on its associated increase in tubular cell proliferation without regard to preceding subcellular degenerative changes. Combing through the published literature from multiple biology disciplines provided insight into the preceding cellular events. Mechanistic pathways involved in the progressive age-related decline in rodent kidney function and several key inflexion points have been identified. These critical pathway factors were then connected using data from renal models from multiple rodent strains, other species, and mechanistic work in humans to form a cohesive picture of pathways and protein interactions. Abundant data linked similar renal pathologies to local events involving hypoxia (hypoxia-inducible factor 1α), altered intrarenal renin–angiotensin system (RAS), oxidative stress (nitric oxide), and pro-inflammatory pathways (transforming growth factor β), with positive feedback loops and downstream effectors amplifying the injury and promoting scarring. Intrarenal RAS alterations seem to be central to all these events and may be critical to CPN development and progression.